A model-based analysis of the clinical and economic impact of personalising P2Y12-receptor inhibition with platelet function testing in acute coronary syndrome patients - Straub, Niels; Beivers, Andreas; Lenk, Ekaterina; Aradi, Daniel; Sibbing, Dirk (Thrombosis and Haemostasis, 2014)
Although some observational studies reported that the measured level of P2Y12-inhibition is predictive for thrombotic events, the clinical and economic benefit of incorporating PFT to personalize P2Y12-receptor directed antiplatelet treatment is unknown. Here, we assessed the clinical impact and cost-effectiveness of selecting P2Y12-inhibitors based on platelet function testing (PFT) in acute coronary syndrome (ACS) patients undergoing PCI. A decision model was developed to analyse the health economic effects of different strategies. PFT-guided treatment was compared with the three options of general clopidogrel, prasugrel or ticagrelor treatment. In the PFT arm, low responders to clopidogrel received prasugrel, while normal responders carried on with clopidogrel. The associated endpoints in the model were cardiovascular death, stent thrombosis and major bleeding. With a simulated cohort of 10,000 patients treated for one year, there were 93 less events in the PFT arm compared to general clopidogrel. In prasugrel and ticagrelor arms, 110 and 86 events were prevented compared to clopidogrel treatment, respectively. The total expected costs (including event costs, drug costs and PFT costs) for generic clopidogrel therapy were US$ 1,059/patient. In the PFT arm, total costs were US$ 1,494, while in the prasugrel and ticagrelor branches they were US$ 3,102 and US$ 3,771, respectively. The incrementalcost- effectiveness-ratio (ICER) was US$ 46,770 for PFT-guided therapy, US$ 185,783 for prasugrel and US$ 315,360 for ticagrelor. In this model-based analysis, a PFT-guided therapy may have fewer adverse outcomes than general treatment with clopidogrel and may be more cost-effective than prasugrel or ticagrelor treatment in ACS patients undergoing PCI.
Keywords: Clopidogrel; prasugrel; ticagrelor; acute coronary syndrome; cost-effectiveness; health economics; platelet function testing